1999
DOI: 10.1021/ja983116s
|View full text |Cite
|
Sign up to set email alerts
|

Lithium and Sodium Ion Binding Energies of N-Acetyl and N-Glycyl Amino Acids

Abstract: Using a quadrupole ion-trap mass spectrometer with an electrospray ionization source, the Cooks kinetic method has been used to measure the lithium and sodium ion binding energies of the N-acetyl and N-glycyl derivatives of a series of 14 amino acids. For comparison, the gas-phase basicities of the amino acid derivatives were also determined by the kinetic method. The lithium binding free energies range from 47.2 to 56.4 kcal/mol, and the sodium affinities from 30.8 to 41.2 kcal/mol. Comparisons between basici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 47 publications
(73 reference statements)
6
50
1
Order By: Relevance
“…The identified fragments presented above indicate that the sodium adduct may be attached to Ser 5 or Asp 4 side chains. These suggestions are in agreement with previous investigations performed by Feng and co-workers [45]. The authors studied lithium and sodium ion binding energies of Nacetyl and N-glycyl amino acids and concluded that the presence of a coordinating group (e.g., -OH, -CO 2 H) in the amino acid side chain can significantly increase the lithium and sodium binding energies.…”
Section: Determination Of the Additional Deprotonation Site In Neuroksupporting
confidence: 89%
“…The identified fragments presented above indicate that the sodium adduct may be attached to Ser 5 or Asp 4 side chains. These suggestions are in agreement with previous investigations performed by Feng and co-workers [45]. The authors studied lithium and sodium ion binding energies of Nacetyl and N-glycyl amino acids and concluded that the presence of a coordinating group (e.g., -OH, -CO 2 H) in the amino acid side chain can significantly increase the lithium and sodium binding energies.…”
Section: Determination Of the Additional Deprotonation Site In Neuroksupporting
confidence: 89%
“…The Na þ affinities were found to follow the trend: cyclo-glycylglycine < cyclo-alanylglycine < cyclo-alanylalanine < N-acetylglycine < glycylglycine < alanylglycine < glycylalanine < glycylglycine ethyl ester < glycylglycine amide, and the value for GG closely reproduces the value found by Klassen et al Talley et al (2002) also employed the kinetic method to find the binding energies of Na þ to a-and b-amino acids and to their methyl esters, and those values were lower with respect to the Li þ affinities of the same ligands (see previous section). The same trend was found by Feng, Gronert, & Lebrilla (1999), who determined the lithium-and sodium-binding energies of the N-acetyl and N-glycyl derivatives of a series of 14 amino acids.…”
Section: B Sodiumsupporting
confidence: 79%
“…BDEs determinations performed by the kinetic method (Cerda & Wesdemiotis, 1996) and by threshold-CID (Rodgers & Armentrout, 2000b) display a reasonable agreement. Moreover, the Cooks' kinetic method was employed to find the Li þ binding energies of the N-acetyl and N-glycyl derivatives of a series of 14 amino acids (Feng, Gronert, & Lebrilla, 1999), and for 17 different aand b-amino acids and their methyl esters (Talley et al, 2002). In this latter case, it was found that the methyl derivatives bind more strongly than the correspondent amino acids, with the exception of proline, which forms salt bridges with Li þ .…”
Section: A Lithiummentioning
confidence: 99%
“…Similarly, the relative intensity of the Li + and Na + adducts ion II is the most abundant (100%) when the C-terminal amino acids are aromatic amino acids, such as Compounds 1, 8, 12, and 13. It seems that Li + and Na + presumably coordinate with the hydroxyl or aryl group of the C-terminal amino acid residues to form an energetically favorable chelate ring by the donation of aromatic π-electrons or lone pair of hydroxyl oxygen atom to the cationic center respectively [55][56][57][58], while in our case, K + shows such ability to a moderate extent (Scheme 7).…”
Section: Resultsmentioning
confidence: 67%